Effect of craniovertebral decompression on CSF dynamics in Chiari malformation type I studied with computational fluid dynamics: Laboratory investigation. - Linge, Svein O; Mardal, Kent-A; Helgeland, Anders; Heiss, John D; Haughton, Victor (Journal of Neurosurgery: Spine, 2014)
Object: The effect of craniovertebral decompression surgery on CSF flow dynamics in patients with Chiari malformation Type I (CM-I) has been incompletely characterized. The authors used computational fluid dynamics to calculate the effect of decompression surgery on CSF flow dynamics in the posterior fossa and upper cervical spinal canal.Methods: Oscillatory flow was simulated in idealized 3D models of the normal adult and the CM-I subarachnoid spaces (both previously described) and in 3 models of CM-I post-craniovertebral decompressions. The 3 postoperative models were created from the CM model by virtually modifying the CM model subarachnoid space to simulate surgical decompressions of different magnitudes. Velocities and pressures were computed with the Navier-Stokes equations in Star-CD for multiple cycles of CSF flow oscillating at 80 cycles/min. Pressure gradients and velocities were compared for 8 levels extending from the posterior fossa to the C3-4 level. Relative pressures and peak velocities were plotted by level from the posterior fossa to C3-4. The heterogeneity of flow velocity distribution around the spinal cord was compared between models.Results: Peak systolic velocities were generally lower in the postoperative models than in the preoperative CM model. With the 2 larger surgical defects, peak systolic velocities were brought closer to normal model velocities (equal values at C-3 and C-4) than with the smallest surgical defect. For the smallest defect, peak velocities were decreased, but not to levels in the normal model. In the postoperative models, heterogeneity in flow velocity distribution around the spinal cord increased from normal model levels as the degree of decompression increased. Pressures in the 5 models differed in magnitude and in pattern. Pressure gradients along the spinal canal in the normal and CM models were nonlinear, with steeper gradients below C3-4 than above. The CM model had a steeper pressure gradient than the normal model above C3-4 and the same gradient below. The postoperative models had lower pressure gradients than the CM model above C2-3. The most conservative decompression had lower pressure gradients than the normal model above C2-3. The two larger decompression defects had CSF pressure gradients below those in the normal model above C2-3. These 2 models had a less steep gradient above C-3 and a steeper gradient below.Conclusions: In computer simulations, craniovertebral surgical defects generally diminished CSF velocities and CSF pressures.